A case of propylthiouracil induced hepatotoxicity and hemolytic anemia - Atilla ÖKTEN; Zeynel MUNGAN; M. Derya ONUK; Rumeyza TURAN; Oktay YEĞİNSU; Uğur ÇEVİKBAŞ; Kadir DEMİR; Sabahattin KAYMAKOĞLU (Turkish Journal of Gastroenterology, 2019)
-